PENERAPAN ETIKA LAYANAN DALAM PERSPEKTIF KOLABORASI GOVERNANCE PADA PERUSAHAAN DAERAH AIR MINUM SURYA SEMBADA - Meirina wati; Tjijik Rahaju; Muhammad Farid Ma`ruf; Badrudin Kurniawan; Galih Wahyu Pradana (DIA: Jurnal Administrasi Publik, 2018)
The existence of the PDAM is one of the things that must be observed because it is one of the Regional Owned Enterprises that provides public services. The urgency of regional business entities in the form of PDAMs becomes increasingly important, considering that as a business entity, the PDAM does not only function to provide services to the community in the form of clean water. But it is also required to be able to contribute economically to the region, so that the area is able to be independent as the essence of autonomy given to the area. This study was designed using a qualitative and quantitative approach. A qualitative approach was developed in order to provide a comprehensive picture of the cooperation built by the PDAM with other parties. Cooperation is built by basing on the vision, mission and objectives of the PDAM to provide better service. The focus of the research was developed from the stages of collaborative governance proposed by Ratner. While the quantitative approach was developed to explore customer responses related to cooperation established by PDAMs to improve services. The purpose of this study is to create a customer service model based on customer recommendations. This goal is based on a shift in the practice of public services that must be able to respond to customer needs satisfactorily, without violating rules and application of applicable service ethics. In addition, there is also a theoretical shift from government to governance.